SAE Technical Paper Series 2016
DOI: 10.4271/2016-01-1461
|View full text |Cite
|
Sign up to set email alerts
|

Data Acquisition using Smart Phone Applications

Abstract: There are numerous publically available smart phone applications designed to track the speed and position of the user. By accessing the phones built in GPS receivers, these applications record the position over time of the phone and report the record on the phone itself, and typically on the application's website. These applications range in cost from free to a few dollars, with some, that advertise greater functionality, costing significantly higher. This paper examines the reliability of the data reported th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Global Position System (GPS) -During previous testing, it was found that the GPS sample rate for any smart phone tested was a maximum of 1 Hz [9]. For some phone applications, the sample rate was even lower, 1/3 Hz to 1/5 Hz.…”
Section: Harry's Lap Timer: Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global Position System (GPS) -During previous testing, it was found that the GPS sample rate for any smart phone tested was a maximum of 1 Hz [9]. For some phone applications, the sample rate was even lower, 1/3 Hz to 1/5 Hz.…”
Section: Harry's Lap Timer: Data Acquisitionmentioning
confidence: 99%
“…The mid-level applications can potentially acquire better speed, acceleration, and positional data than basic applications because they differ in the way they sample the data and report it. In previous testing, Neale et al showed that conventional health fitness applications such as Map My Fitness allows sampling of GPS data every one to two seconds [5]. A reason for this longer interval in fitness applications is that sampling at shorter intervals requires more data storage as well as battery usage and generally is not required for exercise activities that take 20 or 30 minutes.…”
mentioning
confidence: 99%
“…In the last one decade, smartphone‐based crowdsourcing techniques are often used for collecting public transport‐related data [10]. Owing to recent advances in technology, efficient GPS receivers are provided in smartphones for accurate location tracking [17]. Often, raw positioning GPS data does not match with actual position due to various errors in different mobile modules and the navigation system [1].…”
Section: Introductionmentioning
confidence: 99%